Pengaruh Digital Marketing dan Brand Image Terhadap Keputusan Pembelian Konsumen Brand Fashion Screamous Pada Shopee di RW 09 Komplek Padasuka Indah II Kab. Bandung Barat - Yudiyanto Joko Purnomo; Muhamad Parizki Putra (MANAJEMEN, 2025)
This study investigates the influence of Digital Marketing and Brand Image on consumer purchasing decisions for the Screamous fashion brand on the Shopee platform at RW 09 Komplek Padasuka Indah II, West Bandung Regency. Employing a descriptive and associative research design, data were collected through questionnaires distributed to respondents. The findings indicate that Screamous’ Digital Marketing is categorized as effective but requires greater consistency to positively influence consumers’ lifestyles. Similarly, the Brand Image is considered strong yet has not fully delivered tangible benefits in consumers’ daily lives. The associative analysis reveals that Digital Marketing exerts a positive and significant effect of 19.05% on purchasing decisions, while Brand Image contributes 49.24%. Collectively, both variables have a combined positive and significant impact of 68.29% on consumer purchasing decisions. These results underscore the importance of optimizing digital marketing strategies and strengthening brand positioning to enhance consumer engagement and drive purchasing behavior.